A Love-Based Curriculum: A Preventive Strategy Against Violence and Radicalism in Islamic Boarding Schools - Lubis, Ahmad Hafidz; Zurqoni, Zurqoni; Rahman, Mufiqur; Susmiyati, Sri; Marazi, Hamidullah; Afandi, Afandi (SYAMIL: Journal of Islamic Education, 2025)
This study responds to the growing challenges of violence, hierarchical abuse, gender-based discrimination, and radicalism in pesantren, which underscore the need for alternative educational frameworks grounded in compassion, inclusivity, and justice. It examines the Love-Based Curriculum as a conceptual and practical approach to strengthening Islamic boarding school education in Indonesia. Using a descriptive qualitative library research method, the study analyzes a wide range of academic and policy literature, including classical Islamic thought, national educational philosophy, and contemporary perspectives, to explore how love-based values can prevent violence and reinforce religious moderation. The core novelty of this research lies in its synthesis of three key perspectives Al-Ghazali’s ethical pedagogy, Ki Hajar Dewantara’s humanistic educational philosophy, and Abdurrahman Wahid’s (Gus Dur’s) peace-oriented thought into an integrated framework of the Love-Based Curriculum. The findings indicate that compassion, inclusivity, and justice function as foundational principles for addressing hierarchical abuse, gender-based violence, radicalism, and intolerance in pesantren. Overall, the study highlights the Love-Based Curriculum as a preventive and transformative model that supports child-friendly education and promotes religious moderation amid the spread of exclusivist narratives in the digital era. It recommends institutional support from pesantren leaders and policymakers, as well as further research on practical models of implementation across diverse educational contexts.